How's mental health? Dialogues and reflections on care strategies in Primary Health Care Care - Strategies in APS in Mental Health (Research, Society and Development, 2021)
Understand mental health care strategies in the context of Primary Health Care, from the perspective of a Permanent Commission of Integration Teaching-Service. Research participatory action of qualitative approach, anchored in Paulo Freire's Itinerary of Research as a theoretical-methodological reference, occurred in three moments: thematic investigation, codification / decoding and critical unveiling. Four Cultural Circles were conducted with 21 participants, from July to November, 2018. The participants demonstrated insecurity and technical ignorance, emphasizing diagnoses in Mental Health. They scored strategies such as collective activities, integrative and complementary practices, home visits, continuing education and case discussion. Also frequent referrals to specialties, use of psychotropic and exclusively clinical care. It was revealed the importance of legitimizing the Commission's space, possibilities of permanent education, search for knowledge in Mental Health and provide transformations in their territories. Thus, they re-signified their references and actions to confront the pathological and curativist care.